New fossil Osmylopsychopidae (Neuroptera) from the Early/Middle Jurassic of Kyrgyzstan, Central Asia - Khramov, Alexander V.; Makarkin, Vladimir N. (Zootaxa, 2015)
Four genera and four species of Osmylopsychopidae are described from the Jurassic of Kyrgyzstan, Central Asia: Oligophlebiopsis biramosa gen. et sp. nov. (Early Jurassic of Sogyuty); Osmylopsychoides anteromedialis gen. et sp. nov., Psychostoechotes undulatus gen. et sp. nov. and Osmylopsychostoechus sogulensis gen. et sp. nov. (all from the late Early to early Middle Jurassic of Sai-Sagul). By their poorly-developed outer gradate series of crossveins, these taxa (except O. anteromedialis gen. et sp. nov.) are more similar to Triassic genera than to the Middle/Late Jurassic Osmylopsychopidae (particularly from Daohugou, China). Two isolated hind wings from Sai-Sagul (i.e., Osmylopsychostoechus sp. and Osmylopsychopidae gen. et sp. indet.) are preliminarily assigned to this family.